HUBUNGAN AKTIFITAS FISIK DENGAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI PROLANIS MALEOSAN TOMOHON - Filista Soputan; Beatrix J Podung; I Wayan Gede Suarjana (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Hypertension or high blood pressure is a persistent increase in pressure in the arterial blood vessels, where systolic blood pressure is equal to or above 140 mmHg and diastolic pressure is equal to or above 90 mmHg. Increased blood pressure that lasts for a long time can cause damage to the glands, heart, and brain if not detected early and received adequate treatment, therefore lifestyle changes can help prevent and reduce high blood pressure, one of which is to increase physical activity by exercising in a planned and regular manner. The purpose of this study is to determine whether there is a relationship between physical activity and blood pressure in hypertension patients at Prolanis Maleosan Tomohon. The research method used was descriptive with a quantitative approach with a cross sectional design. the sample studied was 71 respondents consisting of all maleosan tomohon prolanis members. data collection using questionnaires, after which the data were analyzed using univariate and bivariate analysis with the chi square test. the results showed that there was a significant p-value of 0.022 (p < 0.05.) From the results of the study it can be concluded that there is a relationship between physical activity and blood pressure.